Respuesta :
The correct answer is:
B) by finding the factorial of the term number, then adding 3 to the result.
Explanation:
If we add 3 before finding the factorial, for the first term we would have:
(1+3)! = 4! = 4*3*2*1 = 24.
This is not the first term, so this is not accurate.
Finding the factorial of the term number and then adding 3, we would have:
1!+3 = 1+3 = 4
2!+3 = 2*1+3 = 2+3 = 5
3!+3 = 3*2*1+3 = 6+3 = 9
4!+3 = 4*3*2*1+3 = 24+3 = 27
5!+3 = 5*4*3*2*1+3 = 120+3 = 123
This is the correct answer.
B) by finding the factorial of the term number, then adding 3 to the result.
Explanation:
If we add 3 before finding the factorial, for the first term we would have:
(1+3)! = 4! = 4*3*2*1 = 24.
This is not the first term, so this is not accurate.
Finding the factorial of the term number and then adding 3, we would have:
1!+3 = 1+3 = 4
2!+3 = 2*1+3 = 2+3 = 5
3!+3 = 3*2*1+3 = 6+3 = 9
4!+3 = 4*3*2*1+3 = 24+3 = 27
5!+3 = 5*4*3*2*1+3 = 120+3 = 123
This is the correct answer.
Answer:
b. by finding the factorial of the term number, then adding 3 to the result
Step-by-step explanation:
edge 2021
(: